Harnessing the power of bee venom for therapeutic and regenerative medical applications: an updated review - Sadek, Kadry M.; Shib, Naira A.; Taher, Ehab S.; Rashed, Fatema; Shukry, Mustafa; Atia, Gamal A.; Taymour, Noha; El-Nablaway, Mohammad; Ibrahim, Ateya M.; Ramadan, Mahmoud M.; Abdelkader, Afaf; Abdo, Mohamed; et al. (Frontiers in Pharmacology, 2024)
Honeybees have been helpful insects since ancient centuries, and this benefit is not limited to being a honey producer only. After the bee stings a person, pain, and swelling occur in this place, due to the effects of bee venom (BV). This is not a poison in the total sense of the word because it has many benefits, and this is due to its composition being rich in proteins, peptides, enzymes, and other types of molecules in low concentrations that show promise in the treatment of numerous diseases and conditions. BV has also demonstrated positive effects against various cancers, antimicrobial activity, and wound healing versus the human immunodeficiency virus (HIV). Even though topical BV therapy is used to varying degrees among countries, localized swelling or itching are common side effects that may occur in some patients. This review provides an in-depth analysis of the complex chemical composition of BV, highlighting the diverse range of bioactive compounds and their therapeutic applications, which extend beyond the well-known anti-inflammatory and pain-relieving effects, showcasing the versatility of BV in modern medicine. A specific search strategy was followed across various databases; Web of sciences, Scopus, Medline, and Google Scholar including in vitro and in vivo clinical studies.to outline an overview of BV composition, methods to use, preparation requirements, and Individual consumption contraindications. Furthermore, this review addresses safety concerns and emerging approaches, such as the use of nanoparticles, to mitigate adverse effects, demonstrating a balanced and holistic perspective. Importantly, the review also incorporates historical context and traditional uses, as well as a unique focus on veterinary applications, setting it apart from previous works and providing a valuable resource for researchers and practitioners in the field.